CONSORT to community: translation of an RCT to a large-scale community intervention and learnings from evaluation of the upscaled program - Carly Jane Moores; Jacqueline Miller; Rebecca Anne Perry; Lily Lai Hang Chan; Lynne Allison Daniels; Helen Anna Vidgen; Anthea Margaret Magarey (BMC, 2017)
Abstract Background Translation encompasses the continuum from clinical efficacy to widespread adoption within the healthcare service and ultimately routine clinical practice. The Parenting, Eating and Activity for Child Health (PEACH™) program has previously demonstrated clinical effectiveness in the management of child obesity, and has been recently implemented as a large-scale community intervention in Queensland, Australia. This paper aims to describe the translation of the evaluation framework from a randomised controlled trial (RCT) to large-scale community intervention (PEACH™ QLD). Tensions between RCT paradigm and implementation research will be discussed along with lived evaluation challenges, responses to overcome these, and key learnings for future evaluation conducted at scale. Methods The translation of evaluation from PEACH™ RCT to the large-scale community intervention PEACH™ QLD is described. While the CONSORT Statement was used to report findings from two previous RCTs, the REAIM framework was more suitable for the evaluation of upscaled delivery of the PEACH™ program. Evaluation of PEACH™ QLD was undertaken during the project delivery period from 2013 to 2016. Results Experiential learnings from conducting the evaluation of PEACH™ QLD to the described evaluation framework are presented for the purposes of informing the future evaluation of upscaled programs. Evaluation changes in response to real-time changes in the delivery of the PEACH™ QLD Project were necessary at stages during the project term. Key evaluation challenges encountered included the collection of complete evaluation data from a diverse and geographically dispersed workforce and the systematic collection of process evaluation data in real time to support program changes during the project. Conclusions Evaluation of large-scale community interventions in the real world is challenging and divergent from RCTs which are rigourously evaluated within a more tightly-controlled clinical research setting. Constructs explored in an RCT are inadequate in describing the enablers and barriers of upscaled community program implementation. Methods for data collection, analysis and reporting also require consideration. We present a number of experiential reflections and suggestions for the successful evaluation of future upscaled community programs which are scarcely reported in the literature. Trials registration PEACH™ QLD was retrospectively registered with the Australian New Zealand Clinical Trials Registry on 28 February 2017 (ACTRN12617000315314).